PENERAPAN DATA MINING UNTUK ANALISIS POLA PEMBELIAN KONSUMEN DENGAN ALGORITMA FP-GROWTH PADA DATA TRANSAKSI PENJUALAN SPAREPART MOTOR - Saputra, Eka; Fauzi, Rahmat (Computer Science and Industrial Engineering, 2023)
The motorcycle repair shop is one of the factors that guarantees the comfort of using a motorcycle. Without a repair shop, riders will find it difficult to provide routine maintenance and repair their problem motorbikes. The data that has been collected is not only as archival data by the workshop but is utilized as data that is processed as information data that is used to increase sales of motor spare parts. This also has an impact on the utilization of existing sales transaction data because transaction data which is usually used as an archive causes accumulation of data whose benefits are not known, even though if the data is processed properly it can be useful as information used to make decisions in obtaining new knowledge about sales besides that it is difficult to make the right decision to determine the stock of goods based on spare part purchasing patterns, as well as the availability of repair shops in every corner of the city does not necessarily guarantee the comfort of motorbike users because there is no fast and accurate information. To get this information, it can be done using data mining techniques.